Risk of endocrine pancreatic insufficiency in patients receiving adjuvant chemoradiation for resected gastric cancer - MAYADAĞLI, ALPASLAN; Gemici, Cengiz; Sargin, Mehmet; Uygur-Bayramicli, Oya; Mayadagli, Alpaslan; Yaprak, Gokhan; Dabak, Resat; Kocak, Mihriban (My University, 2013)
Background: Adjuvant radiotherapy combined with 5-fluorouracil based chemotherapy has become the new standard after curative resection in high risk gastric cancer. Beside many complications due to surgery, the addition of chemotherapy and radiotherapy as adjuvant treatment may lead to both acute and late toxicities. Pancreatic tissue irradiation during this adjuvant treatment because of incidental and unavoidable inclusion of the organ within the radiation field may affect exocrine and endocrine functions of the organ.